Qualidade de vida relacionada à saúde em pacientes submetidos à prostatectomia - MASSA, Danielle Campos (2018)
Introduction: Prostate cancer (PCa), in Brazil, is the second most common among men. Its incidence rate is higher in developed countries and it occurs often from 65 years old. To diagnose PCa, rectal examination and PSA dosage are required, and it can be confirmed by biopsy. When PCa is verified, the treatment options are surgery, radiotherapy or vigilant observation. Radical Prostatectomy (RP) consists of complete extraction of prostate, prostatic urethra, seminal vesicles and ampullae of the vas deferens, associated or not to bilateral lymphadenectomy. During PCa treatment, patient satisfaction and quality of life are affected due to symptoms such as painful urination, urinary incontinence, sexual dysfunction and intestinal changes. Cancer produces a big impact on patient's life and assessing his welfare is important for a more humanistic approach, aiming develop strategies to reduce the unwanted effects of the disease. Objective: to evaluate the Health-Related Quality of life (HRQoL) of patients who are in the late postoperative period of prostatectomy and factors related to possible changes in the urinary, intestinal, sexual and hormonal standards. Methodological procedures: utilization of transversal observational study with a quantitative approach. For data collection, two instruments were used: one for sociodemographic and clinical characterization of the patients; and Expanded Prostate Cancer Index Composite (EPIC) questionnaire to evaluate the domains of urinary function, intestinal habits, sexual function and hormonal function. The interview script was submitted to descriptive analysis. The bivariate analysis for dichotomous predictors was used for the Mann-Whitney test and the analysis of quantitative and ordinal predictors included, respectively, Pearson correlation and Spearman. The simultaneous contribution of demographic and clinical predictors included multiple linear regression analysis. A level of significance of α = 0.05 was considered. Results: 70 patients participated of the study. Participant’s age were from 45 up to 86 years old and the mean age were 67 years old. Prevalence of the patients had no family history of PCa, married, white skin, retired, with incomplete elementary school level, with monthly income of one minimum salary and with two to three dependents. Regarding the maximum complaint by function, 11.4% reported very problematic for urinary function; 4.3% moderately problematic for intestinal habit and 47.1% very problematic for sexual function. It was found that 78.6% rarely or never felt depressed and 77.1%10 of patients rarely or never had a lack of energy. Conclusions: the greatest impact on the HRQoL of the prostatectomized patient was related to the sexual function. Evaluating the HRQoL is important to verify the results obtained from the available treatments. It’s impossible think of increasing the patient's survival without having the least quality of life.